Illegal earnings - Goudkamp, J; Mayr, L (De Gruyter, 2018)
This article addresses the law governing claims in respect of lost illegal earnings. It focuses on common law jurisdictions (and the law in the United Kingdom in particular) where such claims, despite being commonplace, have been largely ignored by academics. It describes the existing law and calls in aid in this regard a four-fold taxonomy of cases. The article then turns attention to how claims in respect of lost illegal earnings ought to be decided. At this juncture, the article looks to ideas emanating from German tort law, which has developed a highly sophisticated jurisprudence on the subject of illegal earnings. The German approach, stated simply, requires tort law to defer to rules in other departments of private law. If, for example, contract law would not protect an interest that a claimant has in a particular transaction by reason of the transaction being tainted with illegality, tort law will not allow a claimant indirectly to obtain the benefits of that transaction via a claim for lost illegal earnings. It is argued that the German solution holds considerable promise and merits serious consideration as an alternative to the significantly more complicated principles that common law courts have developed, which principles currently lack any thoroughgoing rationalisation.